A NIRCam-dark galaxy detected with the MIRI/F1000W filter in the MIDIS/JADES Hubble ultra deep field - Perez-Gonzalez, Pablo G.; Rinaldi, Pierluigi; Caputi, Karina I.; Álvarez-Márquez, Javier; Annunziatella, Marianna; Langeroodi, Danial; Moutard, Thibaud; Boogaard, Leindert; Iani, Edoardo; Melinder, Jens; Costantin, Luca; Östlin, Göran; et al. (The astrophysical journal. Part 2, Letters, 2024)
We report the discovery of Cerberus, an extremely red object detected with the MIRI Deep Imaging Survey (MIDIS) observations in the F1000W filter of the Hubble Ultra Deep Field. The object is detected at signal-to-noise ratio (S/N) ∼ 6, with F1000W ∼ 27 mag, and undetected in the NIRCam data gathered by the JWST Advanced Deep Extragalactic Survey (JADES), fainter than the 30.0-30.5 mag 5σ detection limits in individual bands, as well as in the MIDIS F560W ultradeep data (∼29 mag, 5σ). Analyzing the spectral energy distribution built with low-S/N (<5) measurements in individual optical-to-mid-infrared filters and higher-S/N (≳5) measurements in stacked NIRCam data, we discuss the possible nature of this red NIRCam-dark source using a battery of codes. We discard the possibility of Cerberus being a solar system body based on the <0.″016 proper motion in the 1 yr apart JADES and MIDIS observations. A substellar Galactic nature is deemed unlikely, given that the Cerberus’s relatively flat NIRCam-to-NIRCam and very red NIRCam-to-MIRI flux ratios are not consistent with any brown dwarf model. The extragalactic nature of Cerberus offers three possibilities: (1) a z ∼ 0.4 galaxy with strong emission from polycyclic aromatic hydrocarbons—the very low inferred stellar mass, M ⋆ = 105-106 M ⊙, makes this possibility highly improbable; (2) a dusty galaxy at z ∼ 4 with an inferred stellar mass M ⋆ ∼ 108 M ⊙; and (3) a galaxy with observational properties similar to those of the reddest little red dots discovered around z ∼ 7, but Cerberus lying at z ∼ 15, with the rest-frame optical dominated by emission from a dusty torus or a dusty starburst.